2019
DOI: 10.1186/s13046-019-1390-x
|View full text |Cite
|
Sign up to set email alerts
|

Long non-coding RNA LINC00174 promotes glycolysis and tumor progression by regulating miR-152-3p/SLC2A1 axis in glioma

Abstract: Background Long non-coding RNA plays a crucial role in the occurrence and progression of glioma. We aimed to explore the function of LINC00174 in cell proliferation, apoptosis, migration, invasion and glycolysis of glioma cells, and investigate the molecular mechanism involved. Methods LINC00174 expression in glioma tissues and peritumoral brain edema (PTBE) tissues was examined by RT-qPCR and in situ hybridization. The CCK-8, TUNEL, wound healing, transwell, and ELISA … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
50
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 68 publications
(58 citation statements)
references
References 30 publications
7
50
1
Order By: Relevance
“…Another study initiated by Shen and colleagues then demonstrated that LINC00174 promotes colorectal cancer by regulating miR-1910 [27]. More recently, Shi and colleagues have reported that LINC00174 promotes cell proliferation, migration and apoptosis in part by the regulation of miR-152 in glioma [16]. In the present study, we found the expressions of miR-4500 was regulated by LINC00174.…”
Section: Discussionsupporting
confidence: 65%
“…Another study initiated by Shen and colleagues then demonstrated that LINC00174 promotes colorectal cancer by regulating miR-1910 [27]. More recently, Shi and colleagues have reported that LINC00174 promotes cell proliferation, migration and apoptosis in part by the regulation of miR-152 in glioma [16]. In the present study, we found the expressions of miR-4500 was regulated by LINC00174.…”
Section: Discussionsupporting
confidence: 65%
“…Among them, only LINC00174 and a 5-genes mRNAs signature showed a significant prognostic value in TET patients. Interestingly, an oncogenic role for LINC00174 has been previously reported in several cancer types 27,40,41 .…”
Section: Discussionmentioning
confidence: 85%
“…It is well known that the competing endogenous RNA (ceRNA) regulation network is the most frequently reported molecular mechanism to elucidate the function in tumor biology progress [16][17][18][19]. Therefore, miRNA as the pivotal downstream of lncRNA mediated tumorigenesis via regulation of the target gene.…”
Section: Introductionmentioning
confidence: 99%